عوائق الإبداع في الفقه الإسلامي Obstacles to Creativity in Islamic Jurisprudence - هلال (Huda Hilal) هدى (At-Tajdid - Intellectual Refereed Journal, 2013)
مستخلص البحث يحاول هذا المقال أن يستعين بالدارسات الخاصة بالتفكير الإبداعي من أجل تحديد معوقات الإبداع في الدراسات الفقهية من خلال النظر في بعض الأحكام الاجتهادية لبعض المسائل، واستخدام المنهج التحليلي النقدي دراستها. وقد صنفت دراسات عوائق الإبداع إلى ثلاثة أنواع: إدراكية، ونفسية، وثقافية. ويمكن إدراج التركيز على المسألة في ذاتها دون اعتبارات أخرى كالظروف المحيطة وإهمال مقاصد النصوص، والافتراض بصحة الحلّ الواحد، والقول بغلق باب الاجتهاد من ضمن العوائق الإدراكية، كما يمكن اعتبار رفض الرأي الآخر والتعصب المذهبي من قبل العوائق الثقافية. وكذلك يمكن تصنيف الخوف من الوقوع في الخطأ، وتجنب المخاطرة، والشعور بالعجز والنقص أمام الآخرين، وفقدان الحرية الفكرية من باب العوائق النفسية. الكلمات الأساسية: الفقه الإسلامي، الاجتهاد، الإبداع، التفكير الإبداعي، عوائق، معرفية، ثقافية، نفسية. Abstract This essay is an attempt at making use of studies on creative thinking in order to identify the obstacles hindering creativity in Islamic jurisprudence. This has been carried out by looking into some ijtihÉd-based legal rulings and applying a critical and analytical method in assessing them. Studies on creative thinking have classified impediments to creativity into three categories: cognitive, psychological and cultural. Focusing on the issue on itself without taking consideration of other factors such as neglecting the surrounding circumstances and overlooking the revealed texts’ underlying purposes, the assumption of the “just one correct solution,” and the belief that the gate of ijtihÉd has been closed can be considered among the cognitive obstacles, while intolerance to and rejection of differing opinion and fanatic adherence to one’s doctrinal school can be seen as cultural obstacles. Also, fair of committing error, avoidance of risk taking, feeling of incapacity in relation to others and loss of intellectual freedom may constitute psychological obstacles. Key words: Islamic jurisprudence, ijtihÉd, creativity, creative thinking, obstacles, cognitive, cultural, psychological. Abstrak Artikel ini merupakan cubaan dalam menggunakan kajian tentang pemikiran kreatif untuk mengenal pasti halangan-halangan kepada kreativiti dalam perundangan Islam. Ia dibuat dengan menilai hukum-hukum yang ditetapkan berdasarkan ijtihad dan menerusi kaedah yang kritikal dan analitikal dalam penilaian dibuat. Kajian dalam pemikiran kreatif mengklasifikasikan halangan-halangan kreativiti kepada tiga kategori: kognitif, psikologi dan budaya. Tumpuan diberi kepada isu itu sendiri tanpa mengira faktor-faktor lain seperti pengabaian kepada keadaan sekeliling dan tujuan teks-teks, seterusnya andaian yang "hanya satu penyelesaian yang betul," selain kepercayaan bahawa pintu ijtihad sudah ditutup boleh dianggap antara halangan kognitif. Manakala sikap tidak bertoleransi, menolak perbezaan pendapat dan fanatik kepada aliran sendiri boleh dilihat sebagai halangan budaya. Seterusnya, sikap takut melakukan kesilapan, mengelakkan pengambilan risiko, rasa tidak berupaya berhubung dengan orang lain dan kehilangan kebebasan intelek antara halangan psikologi. Kata kunci: Perundangan Islam, ijtihad, kreativiti, Pemikiran kreatif, halangan, Kognitif, Budaya, Psikologi.